Avaliação da qualidade interna de ovos de consumo submetidos a diferentes condições de armazenamento - Roger Wilker Tavares Klein (2010)
It was checked the inner quality of 1152 consumption eggs from three large egg distributors in the state of Minas Gerais. The treatments were arranged in randomized blocks, being repetitions the block, in factorial 3x2x4, with three distributors of eggs, two storage temperatures (ambient and refrigerated) and four storage periods (zero, seven, 14 and 21 days). The parameters of egg quality analysed were Haugh Unit (HU), albumen pH (pH) and for microbiological were analysed total count of mesophilic aerobic (CFU/g), total and thermal coliforms (CFU/g), Salmonella spp., Staphylococcus spp. and yeasts and molds (CFU/g). It was observed decrease of internal quality of eggs with the period of storage. The pH values increased with the period of storage of eggs for all distributors regardless the temperature of storage and, HU values decreased with storage, however it sharply decrease in eggs kept at room temperature for all distributors. The microbiological analyses showed the absence of Salmonella spp. and coagulase positive Staphylococci. However, it was observed the presence of coagulase negative Staphylococci, and also yeasts and molds, besides mesophilic aerobic, total coliforms and thermal which presented some results above the legal standards. It was concluded that the quality of eggs of the three distributors of Minas Gerais had the same standard of internal quality.